Multiple resistance of Conyza sumatrensis to three mechanisms of action of herbicides (Acta Scientiarum. Agronomy, 2020)
Fleabane (Conyza spp.) is an important weed in grain production systems and is currently one of the most problematic weeds in Brazil. An important factor related to weeds such as fleabane is the characteristic of herbicide-resistant biotypes developed under selection pressure, with multiple resistance previously detected for Conyza spp. Thus, the aim of this study was to demonstrate the multiple resistance of Conyza sumatrensis to the herbicides paraquat, glyphosate, and chlorimuron. From the F2 seeds of biotypes with suspected resistance to paraquat, glyphosate, and chlorimuron, dose-response greenhouse experiments were conducted for the three herbicides. Herbicides were applied when the plants had 6-8 leaves that were at a height of 8 cm. At the end of the evaluations, 28 days after application, multiple resistance to paraquat, glyphosate, and chlorimuron was observed, with resistance factors (RF50) for the control of 7.43, 3.58, and 14.35 and for the reduction of dry mass of 2.65, 2.79, and 11.31, respectively. All the established criteria for demonstrating new cases of weed resistance were met; thus, the first case worldwide of a Conyza species with resistance to herbicides with three different mechanisms of action was confirmed.